Acute Diffuse Peritonitis Due to Spontaneous Rupture of an Infected Endometrioma: A Case Report - Petruškevičiūtė, Evelina; Bužinskienė, Diana (Acta medica Lituanica, 2021)
Background. Endometriosis is defined as a chronic, inflammatory, estrogen-dependent gynaecologic disease. It affects approximately 5–10% of reproductive-age women worldwide. Ovarian endometriosis is the most frequent form of this condition. Endometriotic cysts are found in about 17–44% of women diagnosed with endometriosis. It is well known, that ovarian endometriomas can cause infertility and chronic pelvic pain. Enlarging cysts can also cause ovarian torsion. In addition, ovarian endometriosis slightly increases the risk for ovarian cancer. The rupture of endometriotic ovarian cysts is an exceptional complication. According to the literature, the prevalence is less than 3% among women with endometriosis. The rupture of an ovarian endometrioma can cause acute peritonitis, which can lead to sepsis, septic shock and can be lethal. The occurrence of abscesses within an ovarian endometrioma is an extremely rare complication. Generally, the origin of infected endometriotic ovarian cysts is related to the previous invasive procedures involving pelvic organs or the use of intrauterine devices. Also, ovarian abscesses can be caused by the hematogenous or lymphatic spread of bacteria. Although, the literature points out that infection of endometriotic ovarian cysts can develop spontaneously. In these rare cases, reservoir and route of infection remains an enigma. Case report. A 49-year-old female was brought to the emergency room with severe generalized lower abdominal pain (6/10) and three days lasting fever. Abdominal examination revealed diffuse abdominal pain with anterior abdominal wall muscle tension. Painful solid masses were felt on both sides of the uterus during the pelvic examination. Cystic masses were detected in both ovaries during transvaginal sonography. Computer tomography (CT) of the abdomen and pelvis revealed abnormal changes in both ovaries. A small amount of free fluid was found in the pelvic cavity along with thickened pelvic peritoneum. Suspecting acute peritonitis and bilateral tubo-ovarian abscesses, surgical treatment was performed. Lower midline laparotomy with bilateral adnexectomy and abdominal lavage with 4000 ml normal saline were done. The outcome of peritonitis was evaluated using the Mannheim peritonitis index (MPI=17 – low risk of morbidity and mortality). The histopathological examination revealed the diagnosis of bilateral endometriotic cysts complicated with acute inflammation, with associated acute inflammation of both fallopian tubes. Microbiological cultures from the purulent fluid were negative. Conclusions. Although the occurrence of abscesses within an ovarian endometrioma is an extremely rare finding in clinical practice, it has to be considered by gynaecologists because it might result in a surgical emergency that can be life-threatening. Being aware of the risk factors of abscesses within an endometrioma can lead to an early diagnosis of this rare condition and help to avoid serious complications.